Current New Approach in Thoracoscopic Surgery: Non-Intubated Uniportal Video-Assisted Thoracoscopic Surgery (NI-UniVATS) - Agar, Mehmet; Gulcek, Ilham; Kalkan, Muhammed; Ulutas, Hakki; Celik, Muhammet Reha; Aksu, Ahmet; Cakmak, Muharrem (Mdpi, 2025)
Background and Objectives: Non-intubated uniportal video-assisted thoracoscopic surgery (NI-UniVATS) is a minimally invasive technique performed using a single port, allowing the entire surgical procedure to be completed with spontaneous breathing without the need for general anesthesia. Materials and Methods: This retrospective study included 51 patients who underwent NI-UniVATS between 2020 and 2023. The intraoperative and postoperative data of patients who underwent NI-UniVATS were evaluated. Results: Among the cases, 37 (72.5%) were male, and 14 (46.6%) were female, with a mean age of 47.73 +/- 20.43 years (range: 18-78 years). The mean operative time was 25.92 +/- 7.31 min. No perioperative complications were observed in any patient. The mean postoperative hospital stay was 4.17 +/- 1.76 days (range: 2-9 days). A right hemithoracic approach was performed in 28 patients (54.9%), whereas a left hemithoracic approach was used in 23 patients (45.1%). The procedures performed included wedge resection in 27 patients (52.9%), biopsy in 22 patients (43.1%), pericardial window creation in one patient (2%), and intrathoracic foreign body removal in one patient (2%). Conclusions: NI-UniVATS allows for safer surgery by preventing the adverse effects and complications associated with general anesthesia. NI-UniVATS can be recommended as a safe and feasible approach for both minor and major thoracic procedures.
Keywords: NI-UniVATS; non-intubated; minimally invasive; uniportal; video-assisted thoracoscopic surgery